If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 4(x + 3) = 26 Reorder the terms: -6x + 4(3 + x) = 26 -6x + (3 * 4 + x * 4) = 26 -6x + (12 + 4x) = 26 Reorder the terms: 12 + -6x + 4x = 26 Combine like terms: -6x + 4x = -2x 12 + -2x = 26 Solving 12 + -2x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2x = 26 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 26 + -12 -2x = 26 + -12 Combine like terms: 26 + -12 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| 98-4b=-116 | | 0+5(y)=0 | | 4-3-7(z+1)=6z | | -23+7k=7(k-2)+3k | | 39a+78=33a | | 2x+27-5=54*3 | | 4(x+1)=25+3(x-3) | | 3a+78=33a | | 1=-7*-7+2 | | (18.2-17.5)/17.5= | | x-4y-13=0 | | 3ac+78=33a | | 2*n-3=4*n+1 | | 13(x-9)=-8-5 | | 25y+(-3x)+(-29x)= | | -5-c=35 | | 5=7*-35+2 | | 2(2x+7)+2(x+6)=44 | | 8=7*-54+2 | | 2(x+7)-4(x+3)=15(x-1) | | 1=-1*2+2 | | 7=11-x | | 5n+2-n=-7 | | 5n+2-n=-7 | | -2.6x=32.24 | | 3(0)-5(y)=15 | | -1(5x+8)+3+4x= | | -r=90 | | 3x-11=-68 | | 3(x)-5(0)=15 | | x^2-8x-34=0 | | 20+2k=k-4k |